Economic Dislocation and Recovery in Lebanon - Martelino, Jose (Occasional Papers; Occasional Paper ;, 1995)
This paper provides background information on the Lebanese economy, based on an analysis of the economic consequences of war, and discusses several issues that will be central to Lebanon's prospects for recovery.